Antimicrobial drugstore supply for Cambodian livestock farmers - Heyman, Julia (2020)
Antimicrobial resistance (AMR) has evolved into one of our time’s greatest threats to public health. Antimicrobials are widely used, especially in livestock production where they are also used as growth promoters and for prophylactic purposes. Several countries have begun the process of restricting the use of antimicrobials, but in many places and particularly in low-and middle-income countries (LMICs) the antimicrobial market is poorly regulated, and knowledge about the negative effects of antimicrobial misuse is limited. Antimicrobials are often sold over the counter without the need for prescription, and a low price makes them widely used in all types of animal production. In Cambodia, a consequence of this is a high prevalence of a wide range of resistant bacteria, posing health risks for both people and animals. Another matter to address is the occurrence of falsified and substandard (FS) antimicrobials, leading to treatments with subtherapeutic doses, resulting in treatment failure and further development of AMR. To control the emergence of AMR it is of interest to map the antimicrobial network, in order to identify important stakeholders and suitable points of intervention. In this study interviews were held with retailers at drugstores selling antimicrobials for livestock, namely pigs and poultry. The objective was to obtain information on the retailers’ knowledge about antimicrobials and AMR, and to assess to what extent they are involved in the treatment choice for animals. Antimicrobial samples were also purchased and analysed with mass-spectrophotometry, to verify the content of active pharmaceutical ingredient (API). The results show that retailers take an active part in choosing what antimicrobial to use, and that the general knowledge of antimicrobials and AMR is low. A wide range of antimicrobials are used to treat poultry and pigs, with amoxicillin and enrofloxacin most frequently stated to be among the most sold ones. Many of the substances used are classified by the World Health Organization (WHO) as critically important antimicrobials for human medicine, and the products most often contained at least two different substances. This broadens the product’s treatment spectrum, and can be viewed in light of the current recommendation by WHO to use narrow-spectrum antimicrobials, and whenever possible avoid the use of critically important antimicrobials in livestock. Possible interventions to slow down the development of AMR in Cambodia by reducing and changing the use of antimicrobials, could be by means of education along with strong enforcement of stricter legislation. This survey suggests that retailers at animal drugstores could be a suitable target group for awareness about AMR, since they seem to be influential actors in the antimicrobial network. However, more research is needed to assess the cost-effectiveness of different interventions, especially in LMICs, in order to design measures that are appropriate in the local context.